Evaluation of different chemical groups used for the control of Rhipicephalus microplus against ticks from the Amblyomma cajennense complex parasitizing cattle - Sebastian, Patrick (2026)
The objective of this study was to evaluate the efficacy of different chemical groups, approved as acaricide to Rhipicephalus microplus, against ticks from the Amblyomma cajennense complex parasitizing cattle under laboratory and field conditions. Laboratory trials (LT) used calves artificially infested with Amblyomma tonelliae, while field trials (FT) involved cattle naturally infested with Amblyomma sculptum. Bovines were treated with commercial formulations of amitraz (only FT), doramectin, deltamethrin, fipronil, ivermectin, or a combination of fipronil and ivermectin, using doses recommended for Rhipicephalus microplus control. In the LT, parameters such as attachment, engorgement, feeding period, and reproductive indices were recorded. In the FT, total tick counts, presence of engorged females, infestation prevalence, and efficacy percentage (EP) were assessed. Ivermectin reduced the viability and fertility of A. tonelliae under laboratory conditions but achieved EPs below 60% against A. sculptum in the field. Deltamethrin and doramectin showed low and inconsistent efficacy in both trials. Fipronil completely inhibited engorgement in LT and achieved 59–89% efficacy in FT. The pour-on formulation combining fipronil and ivermectin produced 85–87% efficacy with a rapid knock-down effect. Amitraz was the only formulation providing complete control, reaching 100% efficacy in the FT. Fipronil-based products and particularly amitraz provided the highest levels of control, although the expected residual efficacy of these formulations is low. As a complement to this study, further research to evaluate how different schemes of strategic or sequential application of chemical acaricides to cattle in an annual plan of control could affect the population abundance of Amblyomma species are needed.